2011
DOI: 10.1007/s00520-011-1190-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of HSV, Candida spp., and oral bacteria on the severity of oral mucositis in pediatric acute lymphoblastic leukemia

Abstract: The presence of HSV, mainly HSV-1, and Candida spp. was associated with mucositis severity in pediatric ALL. No association could be found between bacterial CFU and severity of mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 27 publications
1
57
3
2
Order By: Relevance
“…Methodology is similar to our recently published study [17]. The study cohort includes a total of 71 consecutive pediatric ALL patients, enrolled on the Brazilian Childhood Cooperative Group-protocol ALL-99 (GBTLI ALL-99) [18] and treated at the Boldrini Children's Center, from August 2005 to October 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Methodology is similar to our recently published study [17]. The study cohort includes a total of 71 consecutive pediatric ALL patients, enrolled on the Brazilian Childhood Cooperative Group-protocol ALL-99 (GBTLI ALL-99) [18] and treated at the Boldrini Children's Center, from August 2005 to October 2006.…”
Section: Methodsmentioning
confidence: 99%
“…The author concluded that carrying of HSV-1 is a factor exacerbating the intensity of changes in the course of oral mucositis type, but OMI also triggers the virus replication by cytokines secreted by the damaged cells. HSV-seropositive patients more often are exposed to more severe OMI (WHO grades 3 and 4) [6]. Beek et al evaluated the presence of HSV, EBV and CMV in 49 patients treated in 2006-2009 at the University Medical Centre in Leiden, Holland, with haematological malignancies qualified for HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The antineoplastic post-treatment oral affections are compounded when the individual has come from a poor oral health. This condition may be due to several causes, where the lack of information and access to health services are very relevant when surveyed in the literature [13].…”
Section: Discussionmentioning
confidence: 99%